Derivation and validation of a hard-body particle-wall collision model for non-spherical particles of arbitrary shape (2021)
In this work an extended three-dimensional model to describe the process of wall collisions of arbitrary shaped non-spherical particles is developed. This model is derived as the generalized solution of the hard-sphere wall collision model described in Crowe et al. (2012) [1]. The validation of the new model is performed versus experimental results of the collision between cylindrical particles and a flat plate ((Sommerfeld et al., 2015 [2]), Sommerfeld and Lain (2018) [3]). The agreement between the measurements of linear normal and tangential velocities and the model predictions was found to be very good while the rotational velocities forecasted by the model showed also a satisfactory agreement with the experiments.